(untitled) (AYUSHDHARA, 2022)
Skin the outer covering of the body and is the largest part of the body. The skin acts as anatomical barrier from physical, chemical and biological external agent. Due to change in environment, change in lifestyle like change in working schedule increasing work stress which directly affects health so many related factors responsible for skin diseases which is widely include in the heading of “Kushta”. Sidhma kushta is one of the Kushta from Mahakushta characterized by Alabupushpa varna on Urapradesh (chest region), dust like powder on rubbing. By Nidana Doshas get aggravated and they get localised in the superficial layer of skin i.e., Avabhasini. Aggravated Kapha increases the Kleda to produce Swedaavaran and also provide suitable environment for the development of Krimi in it (which is similar to that of pathology of Tinea versicolor). Tinea versicolor (Pityriasis versicolor) is superficial cutaneous fungal skin infection caused by fungus (Malassezia furfur). Raja Prapti is due to Vata diseases. In brief Vata, Kapha, Twak and Raktha involve in the pathogenesis of Sidhma Kushta.